2019
DOI: 10.5296/ijele.v7i2.15339
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Mnemonic-based Instruction on Saudi University Students’ Attitudes Towards Vocabulary Learning

Abstract: Vocabulary learning plays an essential role in foreign language learning. It is also central to language teaching and is of paramount importance to a language learner. Mnemonic is a technique that is used to instruct vocabulary and it helps learners remember better. The association of images and sounds with mnemonics can make it more powerful and effective to help language learners remember better and for a longer time, this can be achieved through applying a method called the keyword method. This study was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…This finding is consistent with Fasih, et al, (2017) study which reported that mnemonic vocabulary instruction increased student engagement and motivation towards new vocabularies. In agreement, studies by Marthila (2019) and by Othman, et al, (2019) both revealed that there was significant effectiveness of using mnemonic technique in teaching vocabulary mastery and that students had positive attitudes towards the mnemonic keyword method that was used to instruct vocabulary. The implication of this is that teachers must use mnemonic instruction that improves recalling of sight, vocabulary words and definitions as well as improve spelling and dictation.…”
Section: Discussionsupporting
confidence: 57%
“…This finding is consistent with Fasih, et al, (2017) study which reported that mnemonic vocabulary instruction increased student engagement and motivation towards new vocabularies. In agreement, studies by Marthila (2019) and by Othman, et al, (2019) both revealed that there was significant effectiveness of using mnemonic technique in teaching vocabulary mastery and that students had positive attitudes towards the mnemonic keyword method that was used to instruct vocabulary. The implication of this is that teachers must use mnemonic instruction that improves recalling of sight, vocabulary words and definitions as well as improve spelling and dictation.…”
Section: Discussionsupporting
confidence: 57%
“…The study also presented a significant improvement in learners' vocabulary learning and retention due to the use of the KWS. Yet, despite the positive implementation of keyword-based strategy in teaching vocabulary (Othman et al, 2019).…”
Section: Kws and Mms Studies In The Saudi Contextmentioning
confidence: 99%